Chitosan-based self-healing protective coatings doped with cerium nitrate for corrosion protection of aluminum alloy 2024 - Carneiro, J.
The good film forming ability, specific solubility and versatile chemical functionalization of chitosan make it a promising candidate for "green" protective coatings. In the present work, these features are exploited together with chitosan high complexing ability to obtain inhibitor-containing anticorrosion coatings for active protection of aluminum alloys. The functionalization of chitosan with fluorinated substituents was also evaluated as a possible route to improve barrier and surface properties of the coating matrix. It was observed that the chitosan layer worked as a reservoir for cationic Ce3+ corrosion inhibitor due to the complexation of Ce3+ with chitosan amino groups, which prevents its uncontrollable and fast leaching. These Ce-containing coatings were found to confer active corrosion protection toward aluminum alloy 2024 as shown by electrochemical impedance spectroscopy. Moreover, the corrosion tests evidence the self-healing ability of prepared chitosan-based "green" protective coatings. The interaction between Ce3+ and chitosan and the concentration effect of the former on the performance of the latter from a corrosion standpoint is also discussed. (C) 2012 Elsevier B.V. All rights reserved.